The Role of Bye-Bye Plastic Bags in Realizing Bali Provincial Government Policy Regarding the Restriction of Plastic Bags in 2013-2018 - Lestari, Gita Permata; Fitri, Tasya Amalia; Hikmawan, M Dian (ijd-demos, 2021)
Abstract:Bye Bye Plastic Bags is an environmental movement that emerged due to the unrest of two young people named Isabel Wijsen and Melati Wijsen regarding the problem of using plastic on the island of Bali because plastic waste on the island of Bali turned out to be found in rice fields and beaches which caused clogged gutters and filled the river. This is a problem in the reality of the environment in Bali should be a concern for local governments and communities. Therefore in this study an analysis will be made on the role of Bye Bye Plastic Bags in realizing the policy of the Provincial Government of Bali in limiting plastic bags in 2013-2018. Theories used in this study are environmental political actors, new social movements and environmental movements and non-government organizations. The method used in this research is a qualitative descriptive approach to explain the journey of Bye Bye Plastic Bags in carrying out its programs and activities so as to realize the policies of the Bali government. The results of the analysis show that the successful activities carried out by Bye Bye Plastic Bags in 2013-2018 in realizing the policy of the Provincial Government of Bali regarding the limitation of plastic bags, namely Spreading Awareness and Education, Creating Policy and Regulation with Government, Showing Solution, and Growing the Movement.Keywords: new social movement, environmental movement, environmental politics.Â Â AbstrakBye Bye Plastic Bags merupakan gerakan lingkungan yang muncul akibat keresahan dua anak muda bernama Isabel Wijsen dan Melati Wijsen terkait masalah penggunaan plastik di pulau Bali karena sampah plastik di pulau Bali ternyata terdapat pada beras. sawah dan pantai yang menyebabkan selokan tersumbat dan memenuhi sungai. Hal ini menjadi masalah dalam realitas lingkungan hidup di Bali yang harus menjadi perhatian pemerintah daerah dan masyarakat. Oleh karena itu dalam penelitian ini akan dilakukan analisis tentang peran Kantong Plastik Bye Bye dalam mewujudkan kebijakan Pemerintah Provinsi Bali dalam pembatasan kantong plastik tahun 2013-2018. Teori yang digunakan dalam penelitian ini adalah para aktor politik lingkungan, gerakan sosial baru dan gerakan lingkungan serta lembaga swadaya masyarakat. Metode yang digunakan dalam penelitian ini adalah pendekatan deskriptif kualitatif untuk menjelaskan perjalanan Kantong Plastik Bye Bye dalam menjalankan program dan kegiatannya guna mewujudkan kebijakan Pemerintah Bali. Hasil analisis menunjukkan bahwa keberhasilan kegiatan yang dilakukan Kantong Plastik Bye Bye tahun 2013-2018 dalam mewujudkan kebijakan Pemerintah Provinsi Bali mengenai pembatasan kantong plastik yaitu Penyebaran Kesadaran dan Edukasi, Membuat Kebijakan dan Regulasi dengan Pemerintah, Menunjukkan Solusi, dan Menumbuhkan Gerakan.Keywords: gerakan sosial baru, gerakan lingkungan, politik lingkungan.